2017
DOI: 10.1039/c7ra04026a
|View full text |Cite
|
Sign up to set email alerts
|

Development of nutrient media to increase the accumulation of lipids without genetic modification of a lipogenic microorganism

Abstract: a Yarrowia lipolytica has drawn attention from the scientists over the last few decades because of its potential to accumulate intracellular lipid that can be transesterified to methyl esters with properties resembling those of diesel. A kinetics study of intracellular lipid production in Y. lipolytica is very important because it would help process modeling and cost minimization for increasing the lipid production. A set of defined media with varying amounts of pure glycerol as the carbon source and a fixed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In this study, the lipid productivity was 1.62±0.11 g/L, without optimization. This lipid productivity is comparable with the results reported by Dobrowolski et al [37], who cultured Y. lipolytica on crude glycerol but lower than reported by Das et al [38], who reported lipid productivity of up to 4 g/L. A much higher lipid productivity of 11.02-16.45 (g/L) was observed when using vegetable oil to cultivate Y. lipolytica YB 423-12 [39].…”
Section: Nutritional Composition Of Yeast Biomass Cultured On Tuna He...supporting
confidence: 88%
“…In this study, the lipid productivity was 1.62±0.11 g/L, without optimization. This lipid productivity is comparable with the results reported by Dobrowolski et al [37], who cultured Y. lipolytica on crude glycerol but lower than reported by Das et al [38], who reported lipid productivity of up to 4 g/L. A much higher lipid productivity of 11.02-16.45 (g/L) was observed when using vegetable oil to cultivate Y. lipolytica YB 423-12 [39].…”
Section: Nutritional Composition Of Yeast Biomass Cultured On Tuna He...supporting
confidence: 88%
“…The addition of this vitamin did not alter the lipid accumulation and growth profile of C. oleaginosus, it has been shown that thiamine metabolism has a crucial role in the lipid accumulation of Y. lipolytica by characterization of thiamine-auxotrophic strain (Walker et al, 2020). On the other hand, the lipid content of Y. lipolytica did not change by supplementing thiamine with a glycerol-based minimal medium (Das et al, 2017).…”
Section: Discussionmentioning
confidence: 99%